2020
DOI: 10.3390/app10093181
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium from Synthetic Wastewater Using Modified Maghemite Nanoparticles

Abstract: The main aim of this study was to ascertain the removal of chromium ions from synthetic wastewater using modified maghemite nanoparticles (MNPs). Commercially available maghemite nanoparticles (NPs) (< 50 nm) were modified using sodium dodecyl sulfate (SDS). The MNPs were characterized using a powder X-ray diffractometer (XRD) and Fourier transform infrared spectrophotometer (FTIR). Statistically designed batch experiments were carried out to evaluate the effects of various parameters, namely the pH of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Behera et al [353] studied the removal of hexavalent chromium based on sodium dodecyl sulfate (SDS)-modified maghemite nanoparticles. The highest removal efficiency of 95.8% was obtained for chromium at a pH of 2.6.…”
Section: Maghemite (γ-Fe 2 O 3 ) Nanoparticlesmentioning
confidence: 99%
“…Behera et al [353] studied the removal of hexavalent chromium based on sodium dodecyl sulfate (SDS)-modified maghemite nanoparticles. The highest removal efficiency of 95.8% was obtained for chromium at a pH of 2.6.…”
Section: Maghemite (γ-Fe 2 O 3 ) Nanoparticlesmentioning
confidence: 99%
“…Pollutants have been released into water from the anthropogenic activities and the consuming polluted water has many disastrous effects on our health. This has created an excessive demand for an effective water treatment technology, adsorption is one of the most effective and powerful purification technique especially for heavy metal ions due to its ease of handling, low cost and high efficiency [1][2][3] . Research work in nanoscale science and engineering has suggested that nanomaterials have a great potential to improve the capability of this technique to reduce water pollutants [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Research work in nanoscale science and engineering has suggested that nanomaterials have a great potential to improve the capability of this technique to reduce water pollutants [4] . Magnetic iron oxides is one type of metallic nanomaterials, that have superior characteristic properties for water treatment 5 especially magnetite (Fe3O4) nanoparticles due to their adsorption/reduction activities, magnetic properties, availability, and susceptibility to modification [2] however, magnetite particles tend to aggregate easily and oxidized in air generally resulting in reduce of adsorption /reduction activities and loss of magnetism and dispersibility. In order to provide the proper solutions to these problems different materials with a high specific surface area were used including clay minerals, zeolites, activated carbon etc.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium (Cr) is a common metallic element in wastewater released from various industries, like electroplating, leather tanning, metal nishing, battery and textiles, etc. (Miretzky et al 2010;Behera SK et al 2020). Although chromium can exist in different oxidation states (from -2 to +6).…”
Section: Introductionmentioning
confidence: 99%